(untitled) (The Research of Medical Science Review, 2025)
Background Cultural competence in nursing is critical for providing patient-centered care, enhancing healthcare outcomes, and eliminating inequities. Nurses must manage varied patient populations to offer effective and respectful care. This study evaluates the cultural competency of nurses in public and private hospitals in Pakistan to find strengths and areas for growth. Methodology A descriptive cross-sectional study was conducted using a structured, pre validated Cultural Competence Self-Assessment Checklist from the Central Vancouver Island Multicultural Society. The study employed a systemic random sampling technique to select 180 registered nurses from Holy Family Hospital Rawalpindi and Rawal General and Dental Hospital Islamabad. Data were collected through self-administered questionnaires. Descriptive and inferential statistical analyses were used to evaluate cultural competence levels and identify factors influencing competency variations. Results The study reveals that nurses exhibit high cultural competency, with 78.3% engaging in courteous cross-cultural interactions and 60% effectively intervening in discrimination cases. However, only 22.8% have strong familiarity with minority communities' histories, emphasizing the importance of professional exposure. Conclusion While nurses in public and commercial institutions frequently practice cultural competence, educational inequalities persist. Improving cultural competency training in nursing education is critical for better patient outcomes, inclusion, and equitable healthcare delivery. Expanding curricula and engaging in continual self-assessment can help nurses deliver culturally relevant care.